2020
DOI: 10.1080/09273948.2020.1799038
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Instrument-based Tests for Detecting and Measuring Vitreous Inflammation in Uveitis: A Systematic Review

Abstract: Purpose: This systematic review aims to identify instrument-based tests for quantifying vitreous inflammation in uveitis, report the test reliability and the level of correlation with clinician grading. Methods: Studies describing instrument-based tests for detecting vitreous inflammation were identified by searching bibliographic databases and trials registers. Test reliability measures and level of correlation with clinician vitreous haze grading are extracted. Results: Twelve studies describing ultrasound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this regard, the vitreous cells, hyalocytes, can be exacerbated in inflamed eyes [40] and vitreous changes are early markers of retinal damage [41]. Several studies have demonstrated the capability of monitoring acute and obvious ocular inflammation in vitreous by OCT and correlated it with retinal disease progression [16,17,21,39,42]. However, this first study opens a window to the possibility of also evaluating subclinical inflammation by vitreous imaging.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In this regard, the vitreous cells, hyalocytes, can be exacerbated in inflamed eyes [40] and vitreous changes are early markers of retinal damage [41]. Several studies have demonstrated the capability of monitoring acute and obvious ocular inflammation in vitreous by OCT and correlated it with retinal disease progression [16,17,21,39,42]. However, this first study opens a window to the possibility of also evaluating subclinical inflammation by vitreous imaging.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…To date, the most promising imaging modality that addresses this need is OCT with ongoing research into its use as a marker of inflammation. 8,[26][27][28][29][30] Spectral domain optical coherence tomography (SD-OCT), the most commonly used OCT technology, derives structural features based on the interaction of light with ocular tissues. 16 The presence of vitreous cells and vitreous haze can be detected by SD-OCT. With regard to cells, Masaaki et al reported a pilot study involving 7 patients with ocular inflammation, in which they showed that reported that cells in the posterior vitreous could not only be imaged but counted to detect changes in inflammation.…”
Section: Oct: Transition To Objective Instrument Based Automated Vitr...mentioning
confidence: 99%
“…Alternative methods of instrument based quantification of vitreous inflammation include ultrasound biomicroscopy (UBM) and retinal photography. 27,[36][37][38][39][40][41] UBM can be utilised to assess the ocular axis from the anterior uvea, to the vitreous base and peripheral retina. Studies using a range of UBM probes demonstrated the feasibility of using this modality in vitreous assessment to detect changes such as vitreoretinal traction and snowbanking.…”
Section: Additional Techniquesmentioning
confidence: 99%